Вивчення молекулярної динамiки конденсованого стану речовини методами спектроскопiї - Otajonov, Sh.; Eshchanov, B.; Isamatov, A. (Publishing house "Academperiodika", 2018)
This work is a logical continuation of our studies [1, 2] and devoted to studying the dependence of molecular interactions of toluene and aniline within the wide range of frequencies. As a result of the statistical treatment of the far parts of the depolarized component spectrum of molecular scattering, it has been shown that the best approximation corresponds to a Gaussian.